Atrial fibrillation outcomes in patients from Asia and non-Asia countries: insights from GARFIELD-AF - Karen Pieper; Xian-hong Fang; Kai Sun; Ajay K Kakkar; Saverio Virdone; Shinya Goto; Gloria Kayani; Zhi-Cheng Jing; John Camm; Chun-Yan Cheng; Tian-Yu Lian; Xi-Jie Zhu; et al. (Open Heart)
Background Differences in the clinical outcomes and level of risk among Asian versus non-Asian patients with atrial fibrillation (AF) have been sparsely investigated.Objective To provide a contemporary prospective comparison of outcomes for newly diagnosed patients with AF, between Asian and non-Asian regions.Methods Six Asian countries (China, Japan, India, Singapore, South Korea and Thailand) and 29 countries outside Asia participated in the Global Anticoagulant Registry in the FIELD-AF (GARFIELD-AF) study. Newly diagnosed patients with AF, enrolled between 2010 and 2016, were followed up for≥2 years. The outcome studies were all-cause, cardiovascular and non-cardiovascular mortality, non-haemorrhagic stroke/systemic embolism (SE), major bleeding. The association of geographical region with clinical outcomes (event rates per 100 person-years) were estimated using multivariable Cox models.Results 13 841/52 057 (26.6%) GARFIELD-AF participants were enrolled in Asia. Average age and prevalence of cardiovascular comorbidities were lower than in non-Asian countries and patients at high risk of stroke (ie, CHA2DS2-VASc≥2 excl. sex) were less frequently anticoagulated (60.1% vs 73.2%). Non-vitamin K oral anticoagulant (NOAC) was similar in both regions (∼28%), though Asian patients were more frequently underdosed. Both Asian and non-Asian patients who received NOAC at enrolment experienced lower all-cause mortality and non-haemorrhagic stroke/SE compared with patients on other treatments or none.All-cause mortality, non-cardiovascular mortality and major bleeding were less frequent in patients from Asia versus non-Asia (HR (95% CI): 0.62 (0.39 to 0.99), 0.52 (0.28 to 0.97), 0.58 (0.36 to 0.96), respectively). Associations of moderate-to-severe chronic kidney disease and vascular disease with increased risk of all-cause mortality were stronger in Asian versus non-Asian patients (interaction p values: 0.0250 and 0.0076, respectively). There was notable heterogeneity in oral anticoagulant (OAC) usage within the Asian countries.Conclusions Patients in Asian countries had a lower risk of all-cause mortality and major bleeding compared to the rest of the world. NOAC had evident benefits for reducing mortality and stroke across populations. Further studies on sociocultural impacts on OAC outcomes are needed.Trial registration number ClinicalTrials.gov NCT01090362.